PERLINDUNGAN HUKUM TERHADAP PENGGUNA JASA TITIP (JASTIP) MELALUI MEDIA ONLINE - Monarchi, Try Krisna; Ismi, Hayatul; Dasrol, Dasrol (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2020)
Development of online shopping systems has created new business opportunities, one of which is known by the public as entrusted services. A entrusted service is a job in and out of a shop, mall or wholesaler with certain brands according to the desires of customers who believe in their services. The goods you are looking for are not only at the local level, there is often a demand for goods from abroad. The entrusted service profession uses a very simple working mechanism. The position of an entrusted service is a third party between the seller and the buyer, but the main task of entrusting services is the shopper for the entrusters. Jastip, which is short for "entrusted services", has recently become a widespread phenomenon in Indonesia.The law does not in detail regulate this online entrusted service activity, but in the laws and regulations in Indonesia Online buying and selling transactions are regulated in Law Number 19 of 2016 concerning amendments to Law Number 11 of 2008 concerning Information and Technology Electronics and Government Regulation Number 71 of 2019 concerning Implementation of Electronic Systems and Transactions and Government Regulation Number 71 of 2019 concerning Implementation of Electronic Systems and Transactions. In its implementation, it regulates Electronic Contracts at least containing certain things, one of which is provisions that give the injured party the right to return goods and / or request product replacement if there are hidden defects.In the implementation of this entrusted service business activity through online media, a problem occurs when consumers who purchase goods using entrusted services experience hidden defects in goods purchased from the entrusted service provider and the seller refuses to provide compensation for the change of goods and / or money changes accordingly. applicable rules. This is certainly contrary to the Consumer Protection Law Number 8 of 1999. In its implementation, business actors have the principle of responsibility in the Consumer Protection law. In cases of violations of consumer rights, careful analysis is needed in analyzing who should be responsible and to what extent the responsibility can be passed on to the parties concerned.The purpose of this study is to determine the mechanism for legal protection and settlement of entrusted service users through online media. And as a suggestion from the author, so that business actors can pay attention to the responsibilities of business actors in carrying out their business activities in accordance with government regulations so that problems do not occur that result in losses to consumers who use these buying and selling services at a later date.Keywords: Legal Protection, Personal Shopper, Online Media, Costumer.